Emotions in University Research Training: Student Experiences and Faculty Perspectives - Torres Esquivel, Luis David; Herrera Castrillo, Cliffor Jerry (Journal of Basic and Applied Psychology Research, 2026)
This study analyzes the emotional factors associated with research training processes among undergraduate students in the Department of Education and Humanities at UNAN-Managua/CUR-Estelí, while also incorporating the faculty perspective on these experiences. It was conducted using a mixed-method, descriptive, cross-sectional approach, involving a questionnaire administered to 395 undergraduate students enrolled in research courses and semi-structured interviews with 34 faculty members responsible for methodological and research components. The results show that students experience emotions such as stress, anxiety, frustration, and insecurity, especially during stages related to goal setting, data analysis, and meeting academic deadlines, while positive emotions such as motivation, satisfaction, and pride emerge in response to significant progress and achievements. From the faculty perspective, factors such as pedagogical guidance, feedback, and emotional support directly influence self-regulation and academic retention. It is concluded that emotions constitute a central component of university research training; therefore, integrating strategies for emotional and pedagogical support is essential for strengthening student well-being, academic resilience, and the quality of research processes in higher education.